The seed composition of arabidopsis mutants for the group 3 sulfate transporters indicates a role in sulfate translocation within developing seeds - Zuber, Hélène; Wirtz, Markus; Hell, Rüdiger (Plant physiology, 2010)
Sulfate is required for the synthesis of sulfur-containing amino acids and numerous other compounds essential for the plant life cycle. The delivery of sulfate to seeds and its translocation between seed tissues is likely to require specific transporters. In Arabidopsis (Arabidopsis thaliana), the group 3 plasmalemma-predicted sulfate transporters (SULTR3) comprise five genes, all expressed in developing seeds, especially in the tissues surrounding the embryo. Here, we show that sulfur supply to seeds is unaffected by T-DNA insertions in the SULTR3 genes. However, remarkably, an increased accumulation of sulfate was found in mature seeds of four mutants out of five. In these mutant seeds, the ratio of sulfur in sulfate form versus total sulfur was significantly increased, accompanied by a reduction in free cysteine content, which varied depending on the gene inactivated. These results demonstrate a reduced capacity of the mutant seeds to metabolize sulfate and suggest that these transporters may be involved in sulfate translocation between seed compartments. This was further supported by sulfate measurements of the envelopes separated from the embryo of the sultr3;2 mutant seeds, which showed differences in sulfate partitioning compared with the wild type. A dissection of the seed proteome of the sultr3 mutants revealed protein changes characteristic of a sulfur-stress response, supporting a role for these transporters in providing sulfate to the embryo. The mutants were affected in 12S globulin accumulation, demonstrating the importance of intraseed sulfate transport for the synthesis and maturation of embryo proteins. Metabolic adjustments were also revealed, some of which could release sulfur from glucosinolates.